Connecting Non-Functional Requirements to Open Source Ecosystems Health - Amorim, Simone da Silva; Mcgregor, John D.; Almeida, Eduardo Santana de; Chavez, Christina von Flach Garcia (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2022: Anais do XVI Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2022)
One efficient way to perceive the effects of design decisions is by analyzing and evaluating Non-Functional Requirements (NFRs). A design decison can contribute positively or negatively toward specific NFRs. In their turn, NFRs describe how the software operates, representing essential quality characteristics of the software systems. In addition, the typical way of perceiving the “quality” of a software ecosystem is through the concept of ecosystem health and its health indicators. Considering the descriptive nature of NFRs representing a quality characteristic of the system, they could be a feasible way to know ecosystem health. Through their connection with the health indicators, it is possible to sketch paths to understand the influence of the NFRs on the health indicators and realize how the ecosystem health perceives the design decisions. This study aims to understand and map influences from NFRs to health indicators based on evidence found in KDE, a real-world ecosystem. We conducted mixed-methods research, including a survey with ecosystem experts and an adapted practitioner-evidence framework. Findings present a high-level descriptive mapping with connections between NFRs and health indicators, besides explaining evidence found in the KDE ecosystem.